Strong Alone, Stronger Together: The Role of Collectivism, Individualism, Egoism, and Self-Efficacy in the Prosocial Behavior of Flood Volunteers: [Strong Alone, Stronger Together: Peran Kolektivisme, Individualisme, Egoisme, dan Efikasi Diri Pada Perilaku Prososial Relawan Banjir] - Shadiqi, Muhammad Abdan; Handayani, Sri Lestari; Azizah, Aulia Nur; Aziza, Laras Aliffya; Mayangsari, Marina Dwi (ANIMA Indonesian Psychological Journal, 2022)
In natural disaster conditions, such as floods, there are always disaster volunteers involved in assisting the people affected. Although this is the case, empirical information related to the prosocial behavior of disaster volunteers (such as during floods) is still limited. Several studies concerning prosocial behavior in Indonesia were more focused on this prosocial behavior using general samples, and those of social volunteers (not in the context of natural disasters). This study was aimed at testing the role of cultural values (collectivism and individualism), self-efficacy, and egoism (egoistic motives), regarding the prosocial behavior of flood volunteers. The authors conducted an online cross-sectional survey, of 150 volunteers involved at the time of the large-scale flood disaster in South Kalimantan, in 2021. In the study, the authors utilized measuring instruments which had already passed through a cross-cultural adaption process, and which have been proven to have satisfactory reliability and validity. The participants were chosen through purposive sampling technique, with the criteria being them having been flood volunteers in South Kalimantan and being 18 years or more of age. The results of bivariate correlation testing indicated that only the values of collectivism and self-efficacy were significantly correlated to prosocial behavior. Multiple regression testing found identical results, that partially, the values of collectivism and self-efficacy significantly predicted prosocial behavior, whilst the other variables (the values of individualism and egoistic motives) were not significant. The results of these findings illustrated that the high level of prosocial behavior by flood volunteers was explained by the presence of the value of the culture of collectivism found in Indonesian culture. Besides this, self-efficacy as flood volunteers was an influential factor in volunteer activities. The values of collectivism and self-efficacy simultaneously and significantly predicted prosocial behavior, with an effect size of R2 = .225. The results of this study have implications for the understanding of, and increasing of the level of, prosocial behavior amongst the public, via the values of a culture of collectivism and of self-efficacy. Pada kondisi bencana alam, seperti banjir, selalu ada relawan bencana yang terlibat menolong masyarakat yang terdampak. Walaupun demikian, penjelasan empiris sehubungan perilaku prososial relawan bencana (seperti saat banjir) masih terbatas. Beberapa studi mengenai perilaku prososial di Indonesia lebih fokus menjelaskan perilaku prososial tersebut pada sampel umum dan relawan sosial (bukan dalam konteks bencana alam). Studi ini bertujuan untuk menguji peran nilai budaya (kolektivisme dan individualisme), efikasi diri, dan egoisme (motif egoistik) terhadap perilaku prososial pada relawan banjir. Penulis melakukan survei cross-sectional secara daring terhadap 150 relawan yang terlibat membantu saat bencana banjir besar di Kalimantan Selatan pada tahun 2021. Dalam studi ini, penulis menggunakan instrumen alat ukur yang telah melewati proses adaptasi lintas budaya dan terbukti memiliki reliabilitas serta validitas yang memuaskan. Partisipan dipilih melalui teknik purposive sampling dengan kriteria pernah menjadi relawan banjir di Kalimantan Selatan dan berusia 18 tahun ke atas. Hasil uji korelasi bivariate menunjukkan bahwa hanya nilai kolektivisme dan efikasi diri yang signifikan berkorelasi dengan perilaku prososial. Uji regresi berganda menemukan hasil yang serupa, secara parsial, nilai kolektivisme dan efikasi diri signifikan memprediksi perilaku prososial, sementara variabel lain (nilai individualisme dan motif egoistik) tidak signifikan. Hasil temuan ini menggambarkan bahwa perilaku prososial para relawan banjir yang tinggi dijelaskan oleh adanya nilai budaya kolektivisme yang melekat pada budaya Indonesia. Selain itu, efikasi diri sebagai relawan banjir menjadi faktor yang berpengaruh pada aktivitas kerelawanan. Nilai kolektivisme dan efikasi diri secara simultan signifikan memprediksi perilaku prososial dengan effect size R2 = 0,225. Hasil studi ini memiliki implikasi untuk memahami dan meningkatkan perilaku prososial di masyarakat melalui nilai budaya kolektivisme dan efikasi diri.